Long-Term Follow-up of Corneal and Sclero-Corneal Grafting in Severe Eye Perforations - S. Biswas, H.P. Adhikary, Qasim Mansoor, Roa Rashad Qamar (Pakistan Journal of Ophthalmology, 2006)
Purpose: The objective of the present study was to assess the prognosis of grossly perforated eyeballs due to pathological condition by attempting a repair with corneal or corneo-scleral graft with anterior segment reconstruction. Material and Method: A retrospective analysis of 26 eyes of 23 patients who underwent free-hand corneal or sclero-corneal graft for perforated eyeballs over a period of 15 years was performed. The minimum follow up period was 3 years, except one patient who died after 4 months from an unrelated cause. The causes of perforations included corneal melt associated with rheumatoid arthritis, chronic non-specific corneal ulcer, rupture of acute hydrops of keratoconus (Down’s syndrome), Herpes zoster keratitis, trauma in a buphthalmic eye, sloughing of the cornea due to Strep. pneumoniae infection and chronic ulcer due to chemical injury. Results: All the patients were able to keep their eyes with a variable amount of vision, except one eye that became phthisical after three months. The patients who did not develop better vision were for various reasons, e.g., pre-existing poor vision, retinal problems and cataract still to be dealt with. Conclusion: The long-term psychological benefits of retaining the eye, preserving a modicum of ocular motility, avoiding enophthalmos which might occur post-enucleation, and in the case of children, facilitation of orbital development make free-hand corneal graft worth considering even in grossly perforated eyeballs due to pathological condition. There is also an uncertain but distinct possibility of restoring a partial degree of vision that might be extremely useful to the patient.